2010
DOI: 10.1088/0004-637x/719/2/1362
|View full text |Cite
|
Sign up to set email alerts
|

Total Solar Eclipse Observations of Hot Prominence Shrouds

Abstract: Using observations of the corona taken during the total solar eclipses of 2006 March 29 and 2008 August 1 in broadband white light and in narrow bandpass filters centered at Fe x 637.4 nm, Fe xi 789.2 nm, Fe xiii 1074.7 nm, and Fe xiv 530.3 nm, we show that prominences observed off the solar limb are enshrouded in hot plasmas within twisted magnetic structures. These shrouds, which are commonly referred to as cavities in the literature, are clearly distinct from the overlying arch-like structures that form the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
65
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 21 publications
(27 reference statements)
13
65
0
1
Order By: Relevance
“…Harvey (2001) reported that cavities are hot plasma inside the filament channels. An extensive discussion of the temperature effects in cavity regions was recently published by Habbal et al (2010Habbal et al ( , 2011; our results tend to confirm their conclusions. In principle, the extension of the cavity channel region can be evaluated, assuming no temporal change, thanks to rotation effects, see figure 13.…”
Section: Iv) Discussion and Conclusionsupporting
confidence: 88%
See 2 more Smart Citations
“…Harvey (2001) reported that cavities are hot plasma inside the filament channels. An extensive discussion of the temperature effects in cavity regions was recently published by Habbal et al (2010Habbal et al ( , 2011; our results tend to confirm their conclusions. In principle, the extension of the cavity channel region can be evaluated, assuming no temporal change, thanks to rotation effects, see figure 13.…”
Section: Iv) Discussion and Conclusionsupporting
confidence: 88%
“…The deficiency values at 195A are surprisingly found to be only about 6.6 %, without taking into account the effect of the spurious scattered light (stray light effect). In this "hotter" emission line of about 1.5 MK the cavity contrast seems reduced, a result similar to the one recently described by Habbal et al (2010 and2011) and by Pasachoff et al (2011) for eclipse cavities. Moreover in Fig.…”
Section: ) Photometric Analysis Of the Cavity Regions In W-l With Ssupporting
confidence: 88%
See 1 more Smart Citation
“…Coronal cavities are often observed to have cooler prominence plasma at their bases (Hudson et al 1999;Gibson et al 2006;Régnier et al 2011). The cavity is a region of relatively low-density high-temperature plasma (Gibson et al 2010;Habbal et al 2010). Berger et al (2011) have proposed that the prominence and its cavity are a form of magneto-thermal convective structure, macroscopically stable, but internally in a constant state of ubiquitous motions (Low et al 2012a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The structure often contains a twisted flux tube able to accumulate magnetic energy and mass within it, which thus can be destabilised by catastrophic mechanisms and/or external triggers. Despite several studies of the thermal structures of cavities especially from white-light coronographs, eclipse observations, EUV, and soft X-ray imaging (e.g., Hudson et al 1999;Hudson & Schwenn 2000;Gibson et al 2006;Habbal et al 2010), there is to our knowledge no observational evidence of a long time series and of high-cadence obsevations of cavity at different temperatures as provided by SDO/AIA data able to (i) clearly demonstrate the thermal structure of both the prominence and cavity material, and (ii) describe how the plasma of a polar-crown filament evolves before and during the eruption. Thus, the observations described here focus for the first time on the dynamics of the inner part of the cavity above the polar crown filament/prominence material and its evolution during the eruptive phase.…”
Section: Introductionmentioning
confidence: 99%